A comparative study between direct torque control technique and field oriented control method for induction motor - Huynh, Thanh Tường; Nguyen, Thuận Hải Đăng; Luong , Hoài Thương; Nguyen Thanh Ngọc; Nguyen, Trường Kỳ; Thach Thị SoChet (Journal of Technical Education Science, 2019)
Three-phase induction motors are widely used in industry because of their advantages such as simple structure, solid, reliable operation, low maintenance and repairs, low-cost and high efficiency. This paper presents a comparative study of field-oriented control (FOC) and direct torque control (DTC) of induction motors using an adaptive flux observer. The main characteristics of field-oriented control and direct torque control schemes are studied by simulation, emphasizing their advantages and disadvantages. The performances of the two control schemes are evaluated in terms of torque, current ripples and transient responses to load toque variations. We can nevertheless observe a slight advance of the DTC scheme compared to FOC scheme regarding the dynamic flux control performance and the implementation complexity. Consequently, the choice of one or the other scheme will depend mainly on specific requirements of the application.